APLIKASI SISTEM INFORMASI GEOGRAFIS (SIG) DAN PENGINDERAAN JAUH UNTUK MODEL HIDROLOGI ANSWERS DALAM MEMPREDIKSI EROSI DAN SEDIMENTASI Studi Kasus : DTA Cipopokol Sub DAS Cisadane Hulu Kabupaten Bogor - Diah Irawati Dwi Arini; Lilik Budi Prasetyo; Omo Rusdiana (Media Konservasi, 2007)
Forest conversion in watershed may lead to erosion, sedimentation, and water quantity fluctuation. Prediction of erosion and sedimentation quantity is one way to describe condition of a watershed. ANSWERS is one of good hydrological model since it can be linked with map. It can formulated the best land use composition and distribution based on simulation. However, most of steps in ANSWERS are conducted manually, especially during thematic map development. The objective of research are (1) to combine the GIS and Remote Sensing in order to reduce technical error during thematic map development, (2) to predict the value of erosion and sedimentation to map the class of erosion and sedimentation range. Research is done in Cipopokol water cathment, Cisadane Hulu sub watershed, Bogor district at June untill October 2005.Keywords: Sedimentation, erosion, water catchment area, GIS, Spatial data